The Effect of Annealing Temperature and Dopant Concentration on the Surface Layer of Vanadium Doped Barium Strontium Titanate (BVST) Thin Film - Siti Norhaida Abdul Rahman (Universiti Malaysia Perlis, 2008)
Access is limited to UniMAP community.